Energia metabolizável de diferentes alimentos para frangos de crescimento lento - Rocha, Josilene Corrêa (2021)
This research was developed with the intention of evaluating the physico-chemical composition, the values of apparent metabolizable energy (EMA) and apparent metabolizable energy corrected by the nitrogen balance (EMAn) of rice bran, corn seed, DDG (dry distillery grain) ), soybean grain, soybean husk and cotton seed, for broilers of the Label Rouge strain in the initial phase. To determine the energy values, the method of total collection of excreta was used. Two metabolizability tests were carried out, from 18 to 21 days of age, for each test 240 slow-growing birds (naked neck) with twelve days of age randomly distributed in metabolic cages, in six replicates of 12 birds each. Both tests consisted of a reference diet based on corn and soybean meal and three test foods. From the 14th day of age, the birds started to receive the experimental diets, with a period of four days of adaptations and, then, four days of total collection of excreta. The collected samples were weighed, homogenized and prepared for analysis of dry matter, nitrogen and crude energy. At the end held analyzes of food, the feed and excreta to determine the composition of foods and apparent metabolizable energy values and apparent metabolizable energy corrected by the nitrogen balance. The content of dry matter, crude protein, mineral matter and crude energy, respectively, in food were: rice bran 88.77%, 14.93%, 5.38% and 4,471 Kcal/Kg; whereas quirera corn presented 88.46%, 7.57%, 1.18% and 3,961 Kcal/Kg; DDG 89.36%, 35.55%, 1.76% and 4,492;soybeans 91.48%, 33%, 11.53% and 4,320 Kcal/Kg; soybean husk 91.29%, 32.20%, 12.65% and 3,764 Kcal/Kg; cotton seed 92,96%, 37.91%, 5% and 5,808 Kcal/Kg. The results of EMA of the foods evaluated based on natural matter determined with slowgrowing chickens of the Label Rouge lineage naked neck in the period from 14 to 21 days of age are: rice bran, 3,679 Kcal/Kg; quirera corn, 3,590 Kcal/Kg; DDG, 2,000 Kcal/Kg; grain soybeans, 2,193 Kcal/Kg; soybean hull, 1,033 Kcal/Kg and cottonseed, 3,774 Kcal/Kg.